Beta-1,4-galactosyltransferase-3 deficiency suppresses the growth of immunogenic tumors in mice - Wei, Heng; Naruse, Chie; Takakura, Daisuke; Sugihara, Kazushi; Pan, Xuchi; Ikeda, Aki; Kawasaki, Nana; Asano, Masahide (Frontiers in Immunology, 2023)
Background: Beta-1,4-galactosyltransferase-3 (B4GALT3) belongs to the family of beta-1,4galactosyltransferases (B4GALTs) and is responsible for the transfer of UDP-galactose to terminal N-acetylglucosamine. B4GALT3 is differentially expressed in tumors and adjacent normal tissues, and is correlated with clinical prognosis in several cancers, including neuroblastoma, cervical cancer, and bladder cancer. However, the exact role of B4GALT3 in the tumor immune microenvironment (TIME) remains unclear. Here, we aimed to elucidate the function of B4GALT3 in the TIME. Methods: To study the functions of B4GALT3 in cancer immunity, either weakly or strongly immunogenic tumor cells were subcutaneously transplanted into wild-type (WT) and B4galt3 knockout (KO) mice. Bone marrow transplantation and CD8 + T cell depletion experiments were conducted to elucidate the role of immune cells in suppressing tumor growth in B4galt3 KO mice. The cell types and gene expression in the tumor region and infiltrating CD8 + T cells were analyzed using flow cytometry and RNA sequencing. N-glycosylated proteins from WT and B4galt3 KO mice were compared using the liquid chromatography tandem mass spectrometry (LC-MS/MS)-based glycoproteomic approach. Results: B4galt3 KO mice exhibited suppressed growth of strongly immunogenic tumors with a notable increase in CD8 + T cell infiltration within tumors. Notably, B4galt3 deficiency led to changes in N-glycan modification of several proteins, including integrin alpha L (ITGAL), involved in T cell activity and proliferation. In vitro experiments suggested that B4galt3 KO CD8 + T cells were more susceptible to activation and displayed increased downstream phosphorylation of FAK linked to ITGAL. Conclusion: Our study demonstrates that B4galt3 deficiency can potentially boost anti-tumor immune responses, largely through enhancing the influx of CD8 + T cells. B4GALT3 might be suppressing cancer immunity by synthesizing the glycan structure of molecules on the CD8 + T cell surface, as evidenced by the changes in the glycan structure of ITGAL in immune cells. Importantly, B4galt3 KO mice showed no adverse effects on growth, development, or reproduction, underscoring the potential of B4GALT3 as a promising and safe therapeutic target for cancer treatment.